Pengaruh Model Pembelajaran Quick On The Draw Berbasis Tri Kaya Parisudha terhadap Hasil Belajar IPA Siswa - Dwipayana, Kadek Ari; Mariana, I Made Alit; Dewi Setiawati, Gusti Ayu (Edukasi: Jurnal Pendidikan Dasar, 2023)
This study aims to determine the effect of the Quick on The Draw learning model based on Tri Kaya Parisudha on the Natural Science Learning Outcomes of Students in Class V SD Negeri 13 Sesetan, Denpasar City. This study used a quasi-experimental research with nonequivalent control group design. The research sample was determined by random sampling technique, in order to obtain 36 students in class VA as the experimental group and 37 students in class VB as the control group. The data collection method uses the test method, with multiple choice tests totaling 30 validated questions. The collected data was normalized using the gain score and then analyzed using the t-test inferential statistics. Based on the results of data analysis, tcount = 5.507 and ttable at a significance level of 5% (α = 0.05) = 1.994. This means tcount > ttable, so that there is a significant difference between groups of students who are taught using the Quick on The Draw learning model based on Tri Kaya Parisudha and groups who are taught using conventional learning. Thus it can be concluded that the Quick on The Draw learning model based on Tri Kaya Parisudha influences the natural science learning outcomes of students in class V SD Negeri 13 Sesetan.